Interlinkages of Fiscal Decentralization, Financial Development, and Carbon Emissions: The Underlying Significance of Natural Resources - Paddu, Abdul Hamid; Reviane, Indraswati Tri Abdi; Saudi, Nur Dwiana Sari; Djam’an, Fitriwati; Zaenal, Mirzalina; Sabbar, Sabbar Dahham (International Journal of Energy Economics and Policy, 2024)
This study investigates a fresh perspective on how natural resource rents (NRR) and quantity of natural resources (QNR) modulate the influence of fiscal decentralization (FD) and the Financial Development Index (FDI) on energy efficiency (ENE) and CO2 Emissions. We draw upon the Stochastic Impacts of Regression on Population, Affluence, and Technology framework, taking the BRICS countries as the subject of investigation from 1986 through 2021. Using a panel Method of Moments Quantile Regression with fixed effects, our results suggest that fiscal decentralization is favorable for environmental stability, particularly in BRICS countries with higher energy efficiency and CO2 Emission levels. Increased FDI proves environmentally harmful, with pronounced effects in more energy-efficient nations. Regarding direct influences, NRR and QNR hinder energy and CO2 efficiency, notably in countries with lower energy efficiency and CO2 emissions. Regarding indirect effects, NRR and QNR positively steer the impact of fiscal decentralization and the Financial Development Index on energy efficiency and CO2 Emissions, exhibiting stronger effects in energy-efficient nations. Among other control variables, Eco-Innovation (ECO_INNO), Solar energy production (SEP), Population (POP), and Economic Growth (GDP) foster environmental stability. We propose that fiscal decentralization should be based on a clear and responsible subnational government framework to counter rent-seeking behaviors and weak environmental conservation. Further, inclusive finance must strengthen the accessibility and cost-effectiveness of financial solutions for economic agents, promoting green consumption and investment initiatives to reach environmental stability and other Sustainable Development Goals.